COMPARISON OF PERIODONTAL STATUS AMONG MILD, MODERATE AND HEAVY SMOKERS IN FACULTY OF DENTISTRY, UNIVERSITAS SUMATERA UTARA: PERBANDINGAN STATUS PERIODONTAL PADA PEROKOK RINGAN, SEDANG DAN BERAT DI FAKULTAS KEDOKTERAN GIGI UNIVERSITAS SUMATERA UTARA - Siti Muthi’atun Naila; Wulandari, Pitu (Dentika: Dental Journal, 2017)
Smoking is associated with a wide spectrum of disease including systemic diseases such as cancer, lung,and cardiovascular disease. Smoking is one of the risk factors that cause the severity of periodontal disease which is influenced by the number of cigarettes consumed per day. This study was aimed to analyze the comparison among periodontal status in mild, moderate, and heavy smokers in the Faculty of Dentistry, Universitas Sumatera Utara. This study was an observational analytic study with the cross-sectional approach,and sampling was done by purposive sampling method. This study was held in PeriodonticsInstallation, USU Dental Hospital (RSGM USU) with a total number of 80 sampleswas selected based on inclusion and exclusion criteria. A questionnaire and informed consent form were distributed to the samples at the beginning of the study followed by oral examination such as Periodontal Index Russell. The analysis data was performed by one way ANOVA test to show the differences in periodontal status among mild, moderate, and heavy smokers. The results showed that there was a significant difference among the mean of periodontal index scores in mild, moderate, and heavy smokers (p<0,05). As a conclusion,the more cigarettes consumed the worse of periodontal status.